An experimental study on the seismic behavior and replaceability of the replaceable steel shear links. (October 2021) - Men, Jinjie; Xiong, Liquan; Wang, Jiachen; Zhang, Qian; He, Pengjie
Abstract: The reinforced concrete columns and steel beams (RCS) composite frames have received popularity in low to moderate seismic regions due to advantages of the system. However, the poor repairable capacity and deteriorating pinched hysteretic behaviour of the traditional RCS framed structure limit the application in practice under earthquakes. This study presents a modified RCS framed structure with replaceable members aiming to enhance the energy dissipation and resilience capability. The structural configuration character and the general predetermined levels of lateral response of the proposed RCS framed structure with replaceable members is first introduced. Seven quasi-static loading tests were subsequently conducted to evaluate the seismic behavior and replaceability of the replaceable shear links. Parameters including the link length ratio, stiffener configuration and link-to-column connection were examined. The test results depicted that the specimens exhibited the shear dominated behavior. The major failure features of the shear links included web-to-stiffener weld tear, web buckling and web fracture. All tested specimen showed a stable bearing strength, large inelastic rotation capacity and excellent energy dissipation behavior. The same link length ratio of the specimens with different specialized connections presented the similar behavior. Noted that end plate and web stiffeners connection can alleviate the stress concentration on the fillet weld of the flange-to-end plate weld and optimize the performance of the shear link. The average overstrength factor and inelastic rotation capacity of the test specimens were 1.9 and 0.087 rad significantly exceeding 1.5 and 0.08 rad provided by the AISC 341-16 provisions for the EBF links, respectively. In addition, the replaceability of the specimens was evaluated underwent the entire loading process. Compared with the T-shaped and Π-shaped plate connections, replacement of the shear link with the end plate demanded the least effort and time.